The effects of individual tree species on species diversity in a tropical dry forest change throughout ontogeny - Gusman Montalvan, E. (2017)
Understanding how diversity is maintained in species-rich communities, such as tropical forests, remains a challenge in ecology. Recent work suggests that the controversy between competing theories could be better resolved by considering the spatial scale at which different processes rule community assembly. Here we use individual species-area relationships (ISAR) to evaluate the spatial organization of tree diversity around individuals of different species in a completely-mapped tropical dry forest in south Ecuador. We test two hypotheses. First, stressful environmental conditions promote facilitative interactions that will generate spatial signals of accumulation of diversity around individual trees - contrary to what has been reported in humid tropical forests. Second, spatial signals will shift through ontogeny. As, as larger, older trees generate new microsite conditions that affect the recruitment of younger, smaller trees. We compute ISAR functions for adult trees, for young trees and a new crossed-ISAR function measuring the accumulation of diversity of young trees around the old trees. We compare observed ISARs to the expectations of inhomogeneous Poisson (i.e. null) models controlling for the effects of environmental variation and habitat association on tree distribution. Although the prevalent response among adult trees was not different from null expectations, which means that the organization of diversity in this size class could be explained by environmental heterogeneity alone, most species accumulated more diversity than expected over short spatial scales in the small stem size class. Only two species accumulated significant diversity in the crossed-ISARs. Our study indicates the role of facilitation in the organization of plant diversity in this dry forest, but that facilitation is limited to some key species acting on early life stages and accumulating diversity around them. Our results demonstrate the benefit of considering different life-stages and crossed analyses to disentangle the processes affecting community assembly in tropical dry forests. © 2015 The Authors.